Change in emotional eating after bariatric surgery: systematic review and meta‐analysis. Issue 6 (16th July 2020) - Wong, L. Y.; Zafari, N.; Churilov, L.; Stammers, L.; Price, S.; Ekinci, E. I.; Sumithran, P.
Abstract : Background: The effect of bariatric surgery on 'emotional eating' (EE) in people with obesity is unclear. This systematic review and meta‐analysis aimed to examine changes in self‐reported emotional eating behaviour after bariatric surgery. Methods: Fifteen electronic databases were searched from inception to August 2019. Included studies encompassed patients undergoing primary bariatric surgery, quantitatively assessed EE, and reported EE scores before and after surgery in the same participants. Studies were excluded if they were not in English or available in full text. The systematic review and meta‐analysis were conducted according to the PRISMA guidelines. Random‐effects models were used for quantitative analysis. Study quality was assessed using the National Heart, Lung, and Blood Institute quality assessment tool for before–after (pre–post) studies with no control group. Results: Some 23 studies containing 6749 participants were included in the qualitative synthesis, with follow‐up of from 2 weeks to 48 months. EE scores decreased to 12 months after surgery. Results were mixed beyond 12 months. Quantitative synthesis of 17 studies (2811 participants) found that EE scores decreased by a standardized mean difference of 1·09 (95 per cent c.i. 0·76 to 1·42) 4–18 months after surgery, indicating a large effect size. Conclusion: Bariatric surgery may mitigate the tendency to eat in response to emotions in the short to medium term. Abstract : In this meta‐analysis involving 17 studies, self‐reported emotional eating scores decreased significantly by a standardized mean difference of 1·09 (95 per cent c.i. 0·76 to 1·42) at 4–18 months after bariatric surgery. This raises the possibility of a mitigating effect of bariatric surgery on emotional eating in the short to medium term. Little evidence of an effect beyond 12 months Abstract : Antecedentes: El efecto de la cirugía bariátrica sobre la "alimentación emocional" ( emotional eating, EE) en personas con obesidad no esta claro. Esta revisión sistemática y metaanálisis tuvo como objetivo examinar los cambios en el comportamiento de la alimentación emocional referida por los mismos pacientes después de cirugía bariátrica. Métodos: Se realizó una búsqueda en 15 bases de datos electrónicas desde el inicio de las mismas hasta agosto de 2019. Los estudios seleccionados incluían pacientes con cirugía bariátrica primaria, EE evaluada de forma cuantitativa, y descripción de las puntuaciones de EE antes y después de la cirugía en los mismos participantes. Se excluyeron estudios que no estuvieran publicados en inglés o si no se disponía del texto completo. Esta revisión sistemática y metaanálisis se llevó a cabo de acuerdo con las recomendaciones PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta-Analyses ). Se utilizó un modelo de efectos aleatorios para el análisis cuantitativo. La calidad de los estudios individuales se evaluó utilizando la herramienta de evaluación de la calidad NHLBI para estudios de antes‐después (pre‐post) sin grupo control. Resultados: Se incluyeron un total de 23 estudios con 6.749 participantes en la síntesis cualitativa, y un seguimiento de 2 semanas a 48 meses. Las puntuaciones EE disminuyeron a los 12 meses postoperatorios. Los resultados fueron variados más allá de los 12 meses. La síntesis cuantitativa de 17 estudios (2.811 participantes) encontró que las puntuaciones EE disminuyeron con una diferencia de medias ponderada de 1, 09 (i.c. del 95% 0, 76, 1, 42) a los 4‐18 meses tras la operación, lo que indica una magnitud de efecto grande. Conclusión: La cirugía bariátrica puede atenuar la tendencia a comer en respuesta a las emociones en el corto y medio plazo.